The ostrich of Pudding Lane - Strong, Jeremy (Edinburgh: Conkers, 2016)
Pudding Lane may be the only primary school in the UK with a real, live ostrich for a mascot. She comes to the school as an escapee from the ostrich farm and soon wins a place in the hearts of staff and pupils alike. Rival schools and Ofsted beware as Pudding Lane prepares to deploy its tall, feathery secret weapon against all comers ... this edition includes jokes, quizzes and trace-and-cut-out activities including false moustaches
Keywords: Children's stories